2x+3(4x-32)=3x-45

Simple and best practice solution for 2x+3(4x-32)=3x-45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3(4x-32)=3x-45 equation:


Simplifying
2x + 3(4x + -32) = 3x + -45

Reorder the terms:
2x + 3(-32 + 4x) = 3x + -45
2x + (-32 * 3 + 4x * 3) = 3x + -45
2x + (-96 + 12x) = 3x + -45

Reorder the terms:
-96 + 2x + 12x = 3x + -45

Combine like terms: 2x + 12x = 14x
-96 + 14x = 3x + -45

Reorder the terms:
-96 + 14x = -45 + 3x

Solving
-96 + 14x = -45 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-96 + 14x + -3x = -45 + 3x + -3x

Combine like terms: 14x + -3x = 11x
-96 + 11x = -45 + 3x + -3x

Combine like terms: 3x + -3x = 0
-96 + 11x = -45 + 0
-96 + 11x = -45

Add '96' to each side of the equation.
-96 + 96 + 11x = -45 + 96

Combine like terms: -96 + 96 = 0
0 + 11x = -45 + 96
11x = -45 + 96

Combine like terms: -45 + 96 = 51
11x = 51

Divide each side by '11'.
x = 4.636363636

Simplifying
x = 4.636363636

See similar equations:

| w+6w=7 | | 8v+8=4(2v+2) | | 8x-4.5+y=31 | | 4(x)=3x-10 | | 4x+6x=54 | | x+10(x)=24 | | 4y^2-8y=x-12 | | -4.5+y=31 | | mx+x=m-2 | | tanx=.1167 | | -9(1+y)y+81(1+y)-1=0 | | 4(a+2)+8=40 | | f(-3)=-1-4 | | log-9x=-1 | | 6(x-5)=3(x+5) | | -x+2(8x+31)=-6 | | 5x-10xy=20 | | 5h-28-3h=32 | | A=a+2b | | log(x-7)+log(x-7)=1 | | 7r-4r+9=7r-r | | log(p+7)=-2 | | 3(x+4)+6(2x-5)=27 | | -72.6=-82.3+x | | 2x^2-2mx+5x+m-3=0 | | -x+98.1=79.4 | | f(x)=(X+8)(x+2) | | 9y^2-81y-1=0 | | 2a+6=8c-12 | | x+(-87.4)=234.6 | | 15+15x= | | (x-3)(x+4)+8=x |

Equations solver categories